Acute Exogenous Lipoid Pneumonitis Following Siphoning of Diesel Fuel: A Case Report - So Yeon Park; Hwan Seok Yong; Seung Kwan Kim; Eun-Young Kang (대한영상의학회지, 2019)
Acute exogenous lipoid pneumonitis is a kind of chemical pneumonitis following the aspiration of volatile hydrocarbon compounds. The clinical and radiological findings are nonspecific. However, it can be diagnosed by the presence of lipid-laden macrophages in bronchoalveolar lavage fluid on the basis of a history of petroleum-based product aspiration. Herein, we report acute exogenous lipoid pneumonitis after unintentional aspiration of diesel fuel during siphonage in a 31-year-old male. Initially the patient had cough, chest pain, and blood-tinged sputum. The purpose of this case report is to review the radiologic manifestations and the previous literatures.